Patterns of Language Use among Immigrant children from Anglophone African Countries living in Botswana. - Umunnakwe, Ngozi (Advances in Social Sciences Research Journal, 2017)
This paper examines the patterns of language use among immigrant children from Anglophone African countries living in Botswana. The study reveals major differences in their patterns of language use when compared to that of their parents. Three distinct language use patterns were identified; namely, children who are monolingual in English; those who are bilingual in English and the mother tongue, English and Kiswahili, or English and Setswana; and a third group who are multilingual in the mother tongue, English, Kiswahili and/ or Setswana. The study also reveals that whereas majority of the immigrant parents do not speak Setswana, in spite of their length of residence in Botswana, a good percentage of their children speaks Setswana. Another interesting finding is that many of the immigrant children who cannot speak their mother tongues are fluent speakers of Setswana, the dominant language of the host community. Data for this study were collected using two instruments; namely, a questionnaire designed for parents and an interview schedule for children aged between 18- 25. The questionnaire was administered to 100 immigrant parents from Ghana, Nigeria, Kenya, Tanzania, and Zambia. Fifty immigrant children from these countries were interviewed to get more insightful data on the patterns of language use among this population. Convenience sampling was used to identify the participants. The theoretical framework of this study was based on the “opportunity versus motivation” argument on language maintenance and language shift. The researcher recommends that immigrant children should be given more exposure and opportunities to learn and speak their mother tongue languages, especially in the family domain.